Effectiveness of Reality Therapy Based on Choice Theory on Marital Intimacy and Satisfaction - Zahra Ebadi; Reza Pasha; Fariba Hafezi; Zahra Eftekhar (Mashhad University of Medical Sciences, 2020)
Background & aim: Dedication to spouse, marriage, and family is one of the most significant factors that has attracted considerable attention in contemporary family and marriage studies to ensure continuity of marriage and the strength of family ties. In the present analysis .The current study aimed at investigating the effectiveness of reality therapy based on choice theory on marital intimacy and satisfaction in Iranian couples. Methods: This pretest-posttest control group design was performed on 40 subjects who referred to counseling centers in Ahvaz in 2018 and were firstly selected by convenience sampling and then randomly assigned to two experimental and control groups (N=20 each). Thompson and Walker's Intimacy Scale and ENRICH marital satisfaction inventory were used for data collection. The experimental group underwent ten 60-minute sessions of reality therapy based on Glasser's choice theory adapted from Amani study (2015); nonetheless, the control group did not receive any interventions. Results: The obtained results demonstrated that reality therapy based on choice theory was effective in increasing intimacy and marital satisfaction among couples (P<0.01). Conclusion: As evidenced by the results of the current study, it is suggested that reality therapy based on choice theory could be incorporated into educational programs for couples and family therapy. Adopting such procedure, therapists can treat communication problems and enrich the intimate relationships among couples and families.